ANALISIS FLYPAPER EFFECT TERHADAP BELANJA DAERAH DI KABUPATEN/KOTA BALI DAN NUSA TENGGARA TAHUN 2014-2018 - Maliyatul Istiqomah; ellyana amran (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
This study aims to analyze the Flypaper Effect on local government expenditure in Bali and Nusa Tenggara in 2014-2018 and to prove whether there is a Flypaper Effect in the region. This study used panel regression analysis with the Eviews 9.0 anaysis tool. The data used in this study are secondary data on the general allocation funds, special allocation funds, profit sharing fund, local government revenue and expenditure of local government for the period of 2014-2018. The results of this study indicate in the regency/municipality of Bali that general allocation funds, special allocation funds and original local government revenue has a positive impact to local government expenditure and Flypaper Effect occurs in districts and municipalities of Bali. while in districts and municipalities of Nusa Tenggara that general allocation funds, special allocation funds, profit sharing funds and original local government revenue has a positive impact to local government expenditure and Flypaper Effect occurs in districts and municipalities of Nusa Tenggara